The Mutual Inhibition of FoxO1 and SREBP-1c Regulated the Progression of Hepatoblastoma by Regulating Fatty Acid Metabolism. (8th September 2021) - Hu, Yu; Zai, Hongyan; Jiang, Wei; Ou, Zhenglin; Yao, Yuanbing; Zhu, Qin
Abstract : Background . Hepatoblastoma (HB) is the most common liver malignancy in pediatrics, but the treatment for this disease is minimal. This study is aimed at exploring the effect of FoxO1 and SREBP-1c on HB and their mechanism. Methods . FoxO1, SREBP-1c, FASN, ACLY, ACC, and MAGL expressions in tissue samples were detected by RT-qPCR and WB. IHC was utilized to measure FASN content. Overexpression and knockdown of FoxO1 and sSREBP-1c were performed on Huh-6 cells. Cell proliferation, migration, and invasion were examined by CCK8, scratch, and transwell assay. ELISA was performed to test the ATP, FAO, NEFA, and Acetyl-CoA contents. ChIP was used to detect the interaction between SREBP-1c protein and the FoxO1 gene. In vivo tumorigenesis was conducted on mice. The morphology of tumor tissue sections was observed by HE staining. Results . FoxO1 expression was downregulated in HB tissue, while the expressions of SREBP-1c, FASN, ACLY, ACC, and MAGL were upregulated. In Huh-6 cells and mouse tumor tissues, FoxO1 knockdown resulted in increased cell proliferation, migration, and invasion and active fatty acid metabolism. On the contrary, after the knockdown of SREBP-1c, cell proliferation, migration, and invasion were weakened, and fatty acid metabolism was significantly reduced. SREBP-1c interacted with the promoter of the FoxO1 gene. When FoxO1 was knocked down, the tumor tissue was more closely packed. After the knockdown of the SREBP-1c gene, the structure of tumor cells was deformed. Conclusion . FoxO1 and SREBP-1c inhibited each other in HB, leading to the increase of intracellular fatty acid metabolism, and ultimately facilitated the development of HB.